Pengaruh Aplikasi Stimulan Terhadap Hasil Produksi Tanaman Karet (Hevea brasiliensis Muell.Arg) Di PT. Socfin Kebun Tanah Besih - Ingrid Ovie Yosephine; Guntoro Guntoro (Agrium, 2019)
Stimulants are a substance used to stimulate the rubber plant to remove more latex than usual. Giving stimulant is usually done on plants aged over 6 years and on slow stater clones such as PB217 stimulant application done in the morning and a sunny day (not rain). Applied to the tapping grooves with lace application technique that is by lubricating the stimulant solution on the tapping groove without pulling scrapnya, in this study water-soluble stimulant or 1 liter of stimulant mixed by 3 liters of water to form a concentration of 2.5% stimulant used Ethrel PA 10. The research was conducted in Afdelling I Kebun Tanah Besih PT. Socfin. The time of this study was conducted in July until August 2017. The results showed that in giving stimulant can increase the production of latex, and lump, it's just DRC decreased dikolakan stimulant solution used has stimulated rubber tree to absorb water more than usual so that greater amount of water than its latex content. Keywords: Lubrication Time, Dose, and Tapping System